HUBUNGAN ANTARA BRAND IMAGE DENGAN MINAT PASIEN UNTUK BEROBAT DI POLIKLINIK ANAK RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Oktariyani, Nina; Marwati, Triyani; Rosyidah, . (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2011)
Background: One important aspect that should be considered by the hospitals to improve patient medication interest is to build a positive brand image in its society. A brand is believed to be able to improve the communication and interaction with consumers. The stronger the brand image, the more powerful interaction with customers, so the more established brand image. The more positive brand image is formed, the higher the patients interest to make a purchase and vice versa, the more negative brand image that is formed, then consumers will tend to look for other alternatives or moved. The purpose of this study was to find out wheter there is a positive correlation between brand image and the interest of patients for medication at child polyclinics Rumah Sakit PKU Muhammadiyah Yogyakarta. Methode: This research used descriptive method with cross sectional approach. Sample of this research was taken from the family of medical patient at children clinic of Rumah Sakit PKU Muhammadiyah Yogyakarta, amounting to 87 people. Measurement of brand image and interests of patients for medication used a questionnaire that had previously been tested on 30 respondents out of subjects. Data analysis using univariate analysis, bivariate, and multivariate. Result: There was a positive influence of brand image with the interests of patients to take a medication at the children clinic of Rumah Sakit PKU Muhammadiyah Yogyakarta as indicated by the value of the correlation coefficient (r) of 0.798 with a significance value of 0.000; Conclusion: There was a positive influence of brand image with the interests of patients to take a medication at the children clinic of Rumah Sakit PKU Muhammadiyah Yogyakarta. Key words: brand image, the interest of patients for medication.